Levels of DNA damage in blood leukocyte samples from non-diabetic and diabetic female rats and their fetuses exposed to air or cigarette smoke - Ortiz Lima, Paula Helena [UNESP]; Damasceno, Débora Cristina [UNESP]; Sinzato, Yuri Karen [UNESP]; Soares de Souza, Maricelma da Silva [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Elsevier B.V., 2008)
dThe objective of the present study was to evaluate DNA damage level in blood leukocytes from diabetic and non-diabetic female Wistar rats exposed to air or to cigarette smoke, and to correlate the findings with levels of DNA damage detected in blood leukocyte samples from their fetuses. A total of 20 rats were distributed into four experimental groups: non-diabetic (control; G1) and diabetic exposed to filtered air (G2): non-diabetic (G3) and diabetic (G4) exposed to cigarette smoke. Rats placed into whole-body exposure chambers were exposed for 30 min to filtered air (control) or to tobacco smoke generated from 10 cigarettes, twice a day, for 2 months. Diabetes was induced by a pancreatic beta-cytotoxic agent, streptozotocin (40 mg/kg b.w.). At day 21 of pregnancy, each rat was anesthetized and humanely killed to obtain maternal and fetal blood samples for genotoxicity analysis using the alkaline comet assay. G2, G3 and G4 dams presented higher DNA damage values in tail moment and tail length as compared to G1 group. There was a significant positive correlation between DNA damage levels in blood leukocyte samples from G2 and G3 groups (tail moment); G3 and G4 groups (tail length) and G3 group (tail intensity) and their fetuses. Thus, this study showed the association of severe diabetes and tobacco cigarette smoke exposure did not exacerbate levels of maternal and fetal DNA damages related with only diabetes or cigarette smoke exposure. Based on the results obtained and taking into account other published data, maternal diabetes requires rigid clinical control and public health and education campaigns should be increased to encourage individuals, especially pregnant women, to stop smoking. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Streptozotocin (STZ); diabetes; comet assay; DNA damage; cigarette smoke; pregnancy